2014
DOI: 10.1073/pnas.1415864111
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-mediated activation of pyrimidine biosynthesis drives UDP–sugar synthesis to support viral protein glycosylation

Abstract: Human cytomegalovirus (HCMV) induces numerous changes to the host metabolic network that are critical for high-titer viral replication. We find that HCMV infection substantially induces de novo pyrimidine biosynthetic flux. This activation is important for HCMV replication because inhibition of pyrimidine biosynthetic enzymes substantially decreases the production of infectious virus, which can be rescued through medium supplementation with pyrimidine biosynthetic intermediates. Metabolomic analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 46 publications
(59 reference statements)
4
87
0
Order By: Relevance
“…Mass spectrometry was performed in negative mode with selected reaction monitoring (SRM)-specific scans as described in DeVito et al (2014) and Munger et al (2008). Further specifics regarding labeling, extraction, chromatography, and mass spectrometry data analysis can be found in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometry was performed in negative mode with selected reaction monitoring (SRM)-specific scans as described in DeVito et al (2014) and Munger et al (2008). Further specifics regarding labeling, extraction, chromatography, and mass spectrometry data analysis can be found in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…7A and B). Others have shown that leflunomide inhibits infectious HCMV production, which can be partially reversed by adding a nucleoside precursor (51). Inhibition of de novo purine or pyrimidine synthesis did not appear to affect the accumulation of the mRNA encoding the HCMV DNA polymerase UL54 (Fig.…”
Section: Deoxyribonucleotides Are Limiting For Hcmv Dna Replicationmentioning
confidence: 82%
“…However, in the last several years, several groups have identified diverse molecules that inhibit pyrimidine biosynthesis and suppress viral growth (A3 and DD264), with cellular profiles suggesting mechanisms of antiviral resistance induction that extend beyond limitation of free nucleosides (Hoffmann et al, 2011; Lucas-Hourani et al, 2013). The antiviral activity of pyrimidine biosynthesis inhibitors such as A3 and DD264 has been demonstrated mainly against RNA viruses (e.g., influenza viruses A and B, Sendai virus, vesicular stomatitis virus, hepatitis C virus, West Nile virus and Dengue I virus), although some activity against DNA viruses (e.g., adenovirus 5, vaccinia, and a polyomavirus) has also been shown (DeVito et al, 2014; Hoffmann et al, 2011; Lucas-Hourani et al, 2013). Consistent with findings in the present study, earlier studies showed that the pyrimidine synthesis inhibitors leflunomide (used clinically as an immunosuppressive anti-rheumatic drug) and A3 have antiviral activity against HIV-1 (Hoffmann et al, 2011; Schlapfer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%